The New Systems Competition - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2001)
While the old systems competition took place with closed borders, globalisation has brought about a new type of systems competition that is driven by the mobility of factors of production. The new systems competition will likely imply the erosion of the European welfare state, induce a race to the bottom in the sense that capital will not even pay for the infrastructure it uses and erode national regulatory systems. In general, it will suffer from the same type of market failure which induced the respective government activity in the first place. The new systems competition will force inefficient governments to seek national efficiency, but national efficiency does not imply that systems competition will itself be efficient.
Keywords: 330; fiscal competition; regulation; immigration